To solve the exercise you can use this property of the absolute value:
![|x|\le a=-a\le x\le a](https://img.qammunity.org/2023/formulas/mathematics/college/ujcekmik1498o2di30bgmahisgqjfaywpo.png)
So, in this case, you have
![|6+9x|\le24=-24\le6+9x\le24](https://img.qammunity.org/2023/formulas/mathematics/college/klofnz8zs9ttdw0m73l25tj2b6lrgm8ota.png)
Then
![\begin{gathered} -24\le6+9x \\ \text{ and} \\ 6+9x\le24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/obto9pauqvvyccrr6q0pd7s4ryw3c9vkgc.png)
To solve the first part you can proceed like this:
![\begin{gathered} -24\le6+9x \\ \text{ Subtract 6 from both sides of the inequality} \\ -24-6\le6+9x-6 \\ -30\le9x \\ \text{ Divide by 9 from both sides of the inequality} \\ -(30)/(9)\le(9x)/(9) \\ -(30)/(9)\le x \\ \text{ Simplify} \\ -(3\cdot10)/(3\cdot3)\le x \\ -(10)/(3)\le x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qb1tvp8ug849f7uw3srck05pyd8q63p3jz.png)
To solve the second part you can proceed like this:
![\begin{gathered} 6+9x\le24 \\ \text{ Subtract 6 from both sides of the inequality} \\ 6+9x-6\le24-6 \\ 9x\le18 \\ \text{ Divide by 9 from both sides of the inequality} \\ (9x)/(9)\le(18)/(9) \\ x\le2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/43qme0cyes3i4ly1w33r0u1h2ai33hg1rf.png)
Therefore, the solution to the inequality will be
![-(10)/(3)\le x\le2](https://img.qammunity.org/2023/formulas/mathematics/college/zdsombd81j89kok9qn74009pbe2z24t2yv.png)
Graphically